The Effects of Physical Exercise on Saliva Composition: A Comprehensive Review - Panagiotis Ntovas; Nikolaos Loumprinis; Panagiotis Maniatakos; Loukia Margaritidi; Christos Rahiotis (MDPI AG, 2022)
Saliva consists of organic and inorganic constituents. During exercise, analysis of the saliva can provide valuable information regarding training stress, adaptation and exercise performance. The objective of the present article was to review the effect of physical exercise on saliva composition. The shift in the composition of the saliva, during and after a workout, reflects the benefits of exercise, its potential risks and the capability of the saliva to serve as a health indicator. The type and the frequency of training, the physical condition and the athletes' general health influence the hormones, immunoglobulins and saliva enzymes. The correlation between saliva and physical exercise has to be further investigated and the available knowledge to be applied for the benefit of the athletes during sports activities.